Implementation of Standard Operating Procedures In Biology Practicum High School - Alfrista Novalia Putri; Febrina Ayu Wulandari; Arum Wilianti Suparno; Arista Mukti Khasanah; Tri Eva Rahmadani; Much. Fuad Saifuddin; Etika Dyah Puspitasari (Bioma : Jurnal Ilmiah Biologi, 2023)
The Laboratory is a room or places equipped with tools and materials suitable for teaching science or implementing science practicum. Laboratory management in terms of organizational structure, activities, and facilities needs to be evaluated to increase awareness of the effectiveness of science learning and increase laboratory safety to the optimum level. This paper aims to determine 1) Standard Operating Procedures and 2) Obstacles in school SOP management. The research method used was descriptive exploratory. The data were collected by conducting interviews, observation, and documentation. The data analysis technique was carried out in descriptive qualitative. The results showed that the Biology Laboratory preparation at three Bantul Regency schools already had a Standard Operating Procedure (SOP). However, some schools have not fulfilled the SOP properly. Of the three schools observed in school C, there is no SOP for storing tools and practicum materials. School B SOP that has not been posted in the open, SOP for occupational health and safety, SOP for procurement of tools or practicum materials, and SOP for purchasing chemicals. School A does not have SOP posted in the open, SOP for storing tools or practicum materials, and procurement of tools or materials.